ChemInform Abstract: Hydrophilic Pd0 Complexes Based on Sugars for Efficient Suzuki—Miyaura Coupling in Aqueous Systems. Issue 9 (March 2015) - Tarantino, Giulia; Curcio, Massimiliano; Pica, Andrea; Carpentieri, Andrea; Cucciolito, Maria E.; Ruffo, Francesco; Vitagliano, Aldo; Lega, Matteo
Abstract Various sugar‐based Pd‐complexes are tested for the Suzuki‐Miyaura coupling and the shown catalyst is the best one.